Enhancing private higher education in Malaysia: An interview with the Former Deputy Director General of the Department of Private Education, Ministry of Education, Ms. Arpah Mohamad. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)

(untitled)
Private higher education institutions (PHEIs) have been active in the Malaysian higher education landscape since early 1980s.